Storm Filomena 8 January 2021. (8th March 2021) - Smart, David
Abstract : Storm Filomena at 1200 utc on 8 January 2021, showing a sub‐section of the WRF model domain. The model's low centre was 998hPa at this time; schematic warm and cold surface fronts are shown conventionally. Wind speeds of over 40ms −1 at 300hPa are shaded pale red and those greater than 60ms −1 at 200hPa are shaded pale blue. The flow vectors depict the ageostrophic wind and the bold contour shows divergence equal to 4 × 10 −5 s −1, both at 300hPa. The axis of the cross‐section shown in Figure 2 is marked by the dashed line and the approximate location of Madrid by 'M'. Abstract : Storm Filomena at 1200 utc on 8 January 2021, showing a sub‐section of the Weather Research and Forecasting model domain.